Mewujudkan Ruang Ibadah Inklusif : Evaluasi Arsitektur Ramah Difabel pada Masjid Kampus UIN Sulthan Tahaha Saifuddin Jambi - Syahidullah Habibie; Saldi Yulistian; Randy Rizal; Brama Nalendra; Shinta Oktaviana (Universitas Medan Area, 2026)
The State Islamic University (UIN) Sulthan Thaha Saifuddin Jambi is one of the largest Islamic universities in Jambi Province and is included in the ten disability-friendly campuses. As an educational institution based on Islamic values, the campus mosque plays a strategic role as a center for student spiritual development, moral strengthening, deepening of Islamic values, and character building. This study aims to identify and evaluate the extent to which the campus mosque facilities of UIN Sulthan Thaha Saifuddin Jambi have implemented accessibility standards and met the principles of friendliness towards people with disabilities. In the process of identifying and analyzing disability-friendly mosques, this study used four accessibility principles: ease, safety, usability, and independence. The method used was descriptive qualitative research with data collection techniques through literature studies and field observations. The study reveals that several campus mosque facilities violate government regulations and are unfriendly to people with disabilities. Based on the results of this assessment, the campus mosque of UIN Sulthan Thaha Saifuddin Jambi cannot be categorized as a disability-friendly campus mosque and still requires further evaluation and development.